Estimating the Economic returns of Education in KSA by using Mincerian Earnings Function - Houcine, Benlaria; Zouheyr, Gheraia (International Journal of Economics and Financial Issues, 2019)
This study aims to measure the economic rate of returns for investment in KSA. by using both basic and extended Mincerian Earnings Function. In addition to this, the comparison had been established between the results obtained and those of other researches in the same domain. We adopted in the research the model of Mincer in evaluating the rate of the economic returns according to previous classifications and the effective experience got by the individual in the work (measured by years). The result of the model application states that the economic return of university education in KSA has been improved by 10.35% based on the benchmark of Psacharopoulos International Return measured by 9.6%. Keywords: The individual Return, Earnings Function, Practical Experience, Theoretical Experience JEL Classifications: I26, J24, J16. DOI: https://doi.org/10.32479/ijefi.8659